Self-Assembly Drugs: From Micelles to Nanomedicine - Messina, Paula Verónica (2014)
Self-assembly has fascinated many scientists over the past few decades. Rapid advances and widespread interest in the study of this subject has led to the synthesis of an ever-increasing number of elegant and intricate functional structures with sizes that approach nano- and mesoscopic dimensions. Today, it has grown into a mature field of modern science whose interfaces with many disciplines have provided invaluable opportunities for crossing boundaries for scientists seeking to design novel molecular materials exhibiting unusual properties, and for researchers investigating the structure and function of biomolecules. Consequently, self-assembly transcends the traditional divisional boundaries of science and represents a highly interdisciplinary field including nanotechnology and nanomedicine. Basically, self-assembly focuses on a wide range of discrete molecules or molecular assemblies and uses physical transformations to achieve its goals. In this Review, we present a comprehensive overview of the advances in the field of drug self-assembly and discuss in detail the synthesis, self-assembly behavior, and physical properties as well as applications. We refer the reader to past reviews dealing with colloidal molecules and colloidal self-assembly. In the first part, we will discuss, compare, and link the various bioinformatic procedures: Molecular Dynamics and Quantitative Structure Activity Relationship. The second section deals with the self-assembly behavior in more detail, in which we focus on several experimental techniques, selected according to the depth of knowledge obtained. The last part will review the advances in drug-protein assembly. Nature provides many examples of proteins that form their substrate binding sites by bringing together the component pieces in a process of self-assembly. We will focus in the understanding of physical properties and applications developing thereof.